28.5k views
4 votes
THANKS! I BEG U PLEASE HELP ME!!!!!!!!!

THANKS! I BEG U PLEASE HELP ME!!!!!!!!!-example-1
User Kas Hunt
by
5.3k points

2 Answers

5 votes
The answer above is correct good luck
User Sanju Menon
by
5.3k points
2 votes
Answer: p = r + 1

Step-by-step explanation:

p = q + 3 and q = r - 2

Substitute q = r - 2 in p = q + 3

Thus,
p = r - 2 + 3
p = r + 1

Therefore, p = r + 1
User Ihsan
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.